Le jugement en matière de lésion de droits de la Chambre de la jeunesse : où en sommes-nous ? - Papillon, Sophie (Les Cahiers de droit, 2015)
Since the coming into force of the Youth Protection Act (YPA), the Court of Québec (Youth Division) has only issued a small number of decisions declaring that the rights of a child have been violated. Notwithstanding the foregoing, children’s rights violations continue to occur. Considering that enforcement of children’s rights is critical to the YPA, it being closely tied to the legislation’s objective, the author examines these type of decisions by analyzing jurisprudence from the last decade while bringing up certain elements for thought. Firstly, the article discusses the notion of children’s rights violation as well as the possible recourses in the event thereof. Secondly, it examines recent decisions, focusing on the type of rights that have been violated, defenses that have been brought forward and corrective measures ordered by the tribunal. The author highlights issues, introduces distinctions and attempts to clarify certain obligations of the different parties involved. A large and liberal interpretation regarding the violation of children’s rights is generally proposed, specifically while considering corrective measures.